Implementasi Model PEMIKAT dalam Meningkatkan Aktivitas, Berpikir Kritis, Kerjasama, dan Hasil Belajar Pendidikan Pancasila Siswa - Nurul Amira; Aslamiah (Mataram University, 2026)
Low levels of student learning activity, critical thinking skills, collaborative skills, and learning outcomes constitute issues that need to be addressed through the implementation of innovative learning models. One viable alternative is the PEMIKAT model, which integrates Problem-Based Learning and the